2013
DOI: 10.1002/tesq.96
|View full text |Cite
|
Sign up to set email alerts
|

“But Before I Go to My Next Step”: A Longitudinal Study of Adolescent English Language Learners' Transitional Devices in Oral Presentations

Abstract: This multiple case study examines patterns in the oral second language use of three Spanish-speaking English language learners in rehearsed presentations produced annually over 4 years (Grades 9-12) in a U.S. high school. Analysis focuses on students' changing use of transitional devices called frame markers (Hyland, 2005) as a lens for understanding language used by school-aged immigrant students in academic settings, the nature of classroom presentations, and the role of a range of contextual factors from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The pedagogical use of OPs has been a popular topic in language teaching research (see Morita, 2000;Hill & Storey, 2003;Kobayashi, 2003;Cheng & Warren, 2005;Jeon, 2005;Tuan & Neomy, 2007;Zappa-Hollman, 2007;Chen, 2009;Bankowski, 2010;Sundrarajun & Kiely, 2010;Tsai, 2010;Yang, 2010;Chou, 2011;Mahmud, 2013;Kibler, Salerno & Palacios, 2014). However, the effect of incorporating video-assisted self-reflection (VASR) in teaching OPs in an EFL (English as a Foreign Language) context has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The pedagogical use of OPs has been a popular topic in language teaching research (see Morita, 2000;Hill & Storey, 2003;Kobayashi, 2003;Cheng & Warren, 2005;Jeon, 2005;Tuan & Neomy, 2007;Zappa-Hollman, 2007;Chen, 2009;Bankowski, 2010;Sundrarajun & Kiely, 2010;Tsai, 2010;Yang, 2010;Chou, 2011;Mahmud, 2013;Kibler, Salerno & Palacios, 2014). However, the effect of incorporating video-assisted self-reflection (VASR) in teaching OPs in an EFL (English as a Foreign Language) context has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, not much research has investigated the use of metadiscourse in academic oral genres such as, AOPs. Metadiscourse studies in oral genre include EAP lessons and university lectures (Lee & Subtirelu, 2015;Yaacob, 2013), text structuring (Thompson, 2003), signalling transitions in OPs (Anthony et al, 2007;Kibler et al, 2014), interpersonal features in lectures (Lee, 2009;Morell, 2007), academic conference (Thompson, 2003), stance in academic speech (Yang, 2014), and interactive strategies in students' academic presentations (Magnuczne Godo, 2006). Evidence suggests that metadiscourse features benefit listeners who can comprehend information presented (Bu, 2014;Hyland, 2005).…”
Section: Metadiscourse Markers In Aopsmentioning
confidence: 99%
“…Several studies have shown how students improve their oral proficiency in the target language (L2) by doing presentations (Kibler et al, 2013;Nejad & Mahfoodh, 2019;Barrett et al, 2020). Okada et al (2017) explain that students can improve their presentation skills by video recording themselves, watching the video to be aware of their strengths and weaknesses, and improving their skills in other presentations.…”
Section: Introductionmentioning
confidence: 99%